Direct delivery of electricity subsidy to farmers in Punjab: will it help conserve groundwater?. Issue 2 (4th March 2022) - Kumar, M. Dinesh; Bassi, Nitin; Verma, Mahendra Singh
ABSTRACT: The article argues that the recently introduced model for the direct delivery of an energy subsidy to well-irrigators in Indian Punjab aimed at incentivizing them to conserve electricity and groundwater is on a weak conceptual footing. Energy quota based on connected load will only lead to the resource-rich appropriating the subsidy benefits. Reduced use of well water to irrigate paddy will not arrest depletion as a large proportion of that water returns to the aquifer. The article suggests some institutional alternatives for bringing about long-term changes in the groundwater balance of Punjab based on sound water-use hydrology and the use of technology and market forces.